Across the River - Dror, Duki; Mevorach, Dalia (Israel : Zygote Films, 2009)
Moshe Rachamim crossed the river alone and left his village a long time ago. No, he carries a great burden upon his shoulders. The journey back to his isolated village reveals the story of a curious young man, who marked the way to the exodus of the Ethiopian Jews, and now, 39 years later, feels he must save his community. For years he has been explaining and preaching about AIDS/HIV, yet the pervasive virus keeps producing victims in the Ethiopian community. Against the ‘silencing’ policy of the Public Health Authority and the denial of the community, Moshe sets out on a mission to expose the disease and stop it from spreading.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films